Application of Total Quality Management (TQM) in the Administration of the El-Barqī Arabic Language Study Institution - Ramdhani, Muhammad Rikza Wahyu Hilal; Fitrah, Isti Jayang; Arista, Dian; Kholid, Nur (Shaut al Arabiyyah, 2025)
The El-Barqī Arabic Language Study Institution implements the concept of Total Quality Management (TQM) in its programme, following Arthur R. Tenner's theory. TQM is guided by three core concepts. The ideas encompassed are as follows: firstly, a strong emphasis on customer focus, where El-Barqī offers extensive resources to educators in order to facilitate and enhance the effectiveness of the learning process. One of these amenities involves the provision of native Arabic speakers to facilitate direct Arabic language communication practice with native speakers. El-Barqī constantly engages with the parents of pupils through Islamic studies. The tangible effect of prioritising customer satisfaction is apparent in the growing annual intake of students and the extensive partnerships established with both public and private institutions by El-Barqī. Additionally, El-Barqī has implemented process improvement measures, including the enhancement of its programmes. This encompasses the implementation of language study programmes, both non-residential and residential, as well as the establishment of the Middle East Study Guidance Programme. Additionally, El-Barqī ensures full engagement, resulting in the production of highly skilled Arabic language graduates who have achieved numerous notable accomplishments. The outstanding collaboration inside El-Barqī has undeniably led to the successful implementation of its programmes. Hence, the adoption of Total Quality Management (TQM) has a substantial influence on enhancing the standard of education.